Parental Interpersonal Communication Skills on Adolescent Reproductive Health - Priska, Maria Alna; Kusumaningrum, Tanjung Anitasari Indah (Jurnal Promosi Kesehatan Indonesia, 2024)
Background: Adolescent reproductive health issues can be prevented and controlled with reproductive health education by families through interpersonal communication between parents and adolescents. In reality, there are still many parents who do not discuss this because the communication skills of parents still lacking. This study aims to obtain an overview of interpersonal communication skills from parents to adolescents regarding adolescent reproductive health in Pajang Village, Surakarta.Method: This type of research is qualitative research with a case study approach of working parents who have provided reproductive health information to adolescents aged 15-19 years. A total of 15 mothers were involved in this study who agreed to conduct semi-structured interviews as a data collection technique. Fifteen adolescents and 15 husbands also conducted semi structured interviews as triangulation informants. Determination of informants using the Purposive Sampling technique.Results: The results showed that the communication skills of parents in the Pajang Village were in accordance with interpersonal communication skills which required openness, empathy, positiveness, supportiveness, and equality when communicating with the other person. It's just necessary for parents to have the willingness to start communicating about reproductive health even if teenagers don't ask questions, increase nonverbal empathy, get used to giving praise or appreciation to teenagers for maintaining their good reproductive health, and are expected to be a credible source of information for teenagers by choosing literacy sources.